Strategies Adopted by Novice Nurse Educators to Facilitate Their Transition From Practice to Academia: A Qualitative Study in Ghana - Timothy Tienbia Laari MPhil, BSc, RN; Felix Apiribu PhD, RN; Timothy Gazari MPhil, RN; Moses Haruna Akor MPhil, RN; Adwoa Bemah Boamah Mensah PhD, RN; Gideon Awenabisa Atanuriba MPhil, RN; Joseph Kuufaakang Kuunibe MPhil, RN; Philemon Adoliwine Amooba MSc, RN (SAGE Publishing, 2021)
Introduction The successful transition of nurses from clinical practice to academia is essential to the training of a proficient future nursing workforce. However, deprived of requisite support and guidance, novice nurse educators often find the transition from bedside nursing practice to the classroom challenging and hence, adopt some coping strategies to facilitate their transition. Yet, little is known about the strategies adopted by Ghanaian novice nurse educators to facilitate their transition. Objective This study explored the strategies adopted by novice nurse educators to facilitate their transition from practice to academia in three nursing training colleges in Ghana. Methods This study adopted a descriptive qualitative study design. The study used a purposive sampling technique to recruit 12 novice nurse educators. Data were generated through individual in-depth interviews using a semistructured interview guide. Interviews were audio-recorded, transcribed verbatim, and analyzed manually through thematic analysis. Results Novice nurse educators adopted a wide range of strategies to facilitate their transition from practice to academia. Four major themes emerged: (1) seeking support from peers, (2) attending workshops and conferences, (3) relying on performance appraisal and feedback, and (4) applying past clinical nursing knowledge. Conclusion The strategies adopted to facilitate the transition were mostly self-inspired and informal, which calls for more formal and evidence-based strategies to facilitate the transition process. College authorities must create, or adopt and modify faculty mentorship models to mentor novice nurse educators, develop and implement college-specific orientation programmes for novice nurse educators, and implement regular online tutor appraisals by students.